Does Hypoxia cause carcinogenic iron accumulation in Alcoholic Liver Disease (ALD)? - Silva, Ines; Rausch, Vanessa; Seitz, Helmut K.; Mueller, Sebastian (Cancers, 2017)
Alcoholic liver disease (ALD) is a leading health risk worldwide. Hepatic iron overload is frequently observed in ALD patients and it is an important and independent factor for disease progression, survival, and the development of primary liver cancer (HCC). At a systemic level, iron homeostasis is controlled by the liver-secreted hormone hepcidin. Hepcidin regulation is complex and still not completely understood. It is modulated by many pathophysiological conditions associated with ALD, such as inflammation, anemia, oxidative stress/H2O2, or hypoxia. Namely, the data on hypoxia-signaling of hepcidin are conflicting, which seems to be mainly due to interpretational limitations of in vivo data and methodological challenges. Hence, it is often overlooked that hepcidin-secreting hepatocytes are physiologically exposed to 2-7% oxygen, and that key oxygen species such as H2O2 act as signaling messengers in such a hypoxic environment. Indeed, with the recently introduced glucose oxidase/catalase (GOX/CAT) system it has been possible to independently study hypoxia and H2O2 signaling. First preliminary data indicate that hypoxia enhances H2O2-mediated induction of hepcidin, pointing towards oxidases such as NADPH oxidase 4 (NOX4). We here review and discuss novel concepts of hypoxia signaling that could help to better understand hepcidin-associated iron overload in ALD.
Gesehen am 08.04.2019